Germination ecology of spiny (Amaranthus spinosus) and slender amaranth (A. viridis): troublesome weeds of direct-seeded rice - Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2009)
Spiny and slender amaranth are troublesome Amaranthaceae species of direct-seeded rice and other upland crops in many Asian countries. Seed germination and seedling emergence response of these species to various environmental factors was determined in laboratory and screenhouse experiments. Germination in both species was stimulated by 35/25 and 30/20 C fluctuating temperatures and light. Germination of slender amaranth was more sensitive to increasing salt and water stress than spiny amaranth. Spiny amaranth germinated at a NaCl concentration of 100 mM (19%), whereas slender amaranth seeds did not germinate at this concentration. In seed burial trials where the seeds were on the soil surface, emergence was 56 and 68% for spiny amaranth and slender amaranth, respectively. Only 7% of spiny amaranth seedling emerged from a soil depth of 0.5 cm, whereas no emergence was observed for 4 cm or deeper. For slender amaranth, 6 and 0% emergence was observed at 4 and 6 cm, respectively. Seedling emergence of spiny amaranth was affected more by high rates of rice residue than slender amaranth. Greater quantities of residue than those normally found in rice fields were required to significantly reduce weed densities.